An Evolutionary Approach to the Annotation of Discharge Summaries. - Lohr, C.; Modersohn, L.; Hellrich, J.; Kolditz, T.; Hahn, U. (Stud Health Technol Inform, 2020)
We here describe the evolution of annotation guidelines for major clinical named entities, namely Diagnosis, Findings and Symptoms, on a corpus of approximately 1,000 German discharge letters. Due to their intrinsic opaqueness and complexity, clinical annotation tasks require continuous guideline tuning, beginning from the initial definition of crucial entities and the subsequent iterative evolution of guidelines based on empirical evidence. We describe rationales for adaptation, with focus on several metrical criteria and task-centered clinical constraints.
Keywords: *Data Curation; Humans; *Patient Discharge